Research on spatial structure and resilience of complex urban network: A case study of Jing-Jin-Ji Urban Agglomeration - Zhang, Yang; Yang, Yang; Wei, Shaokun; Ma, Zijun; Tian, Miao; Sun, Meng; Nie, Jiabin (Frontiers in Environmental Science, 2022)
With the long-term impact of economic globalization, the accelerated cross-border flow of resource elements between cities is increasingly important for the development of urban regions. In this context, the central place theory, which emphasizes the vertical hierarchical relationship between cities, has obvious limitations in interpreting urban interaction. This paper takes the Beijing Tianjin Hebei Urban Agglomeration (including Beijing, Tianjin. and 11 prefecture-level cities in Hebei Province) as the research object, constructs three complex networks of economy, information, and economic information coupling connection, and analyzes the resilience of the network structure. The research results show that: (1) The spatial distribution of the economy, information, and economic information coupling networks of the Beijing Tianjin Hebei Urban Agglomeration shows a spatial pattern with Beijing as the core and radiating outward; (2) In terms of weighted degree distribution, Beijing, as an arrow city, has strong competitiveness in the economy and information network, but the hierarchy of cities with balanced information economy development is low; (3) In terms of weighted degree correlation, among the three networks, the cities with a high weighted degree prefer to connect with cities with a low weighted degree, and the mismatch is ranked as information network > information economy coupling network > economic connection network; (4) In terms of network transmission, information network > economy connection network > information economy coupling network, and Beijing and Tianjin have a greater impact. The above results have strong guidance and practical significance for the formulation and adjustment of territorial spatial planning and regional optimization.